2011
DOI: 10.1002/ptr.3619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ID‐alG on Weight Management and Body Fat Mass in High‐Fat‐Fed Rats

Abstract: Seaweed extract of Ascophyllum nodosum, ID-alG™, was evaluated for its chronic effects on weight management in high-fat-fed Sprague-Dawley rats. ID-alG™ was orally administered daily during 9 weeks at doses of 40 and 400 mg/kg/day with fat-enriched diet (FED) in comparison with two control groups consuming standard diet (negative control) or FED (positive control) and orally treated with vehicle. Body weight, percentage of body fat mass and lipid parameters were measured. After 9 weeks, the oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…No significant differences in HDL-C were observed at the end of the study between the 3 experimental groups. This finding is similar to other studies [40]. However, contradictory results have also been reported where HF feeding significantly decreased HDL-C levels [41].…”
Section: Discussionsupporting
confidence: 92%
“…No significant differences in HDL-C were observed at the end of the study between the 3 experimental groups. This finding is similar to other studies [40]. However, contradictory results have also been reported where HF feeding significantly decreased HDL-C levels [41].…”
Section: Discussionsupporting
confidence: 92%
“…Terpend et al [27] carried out a study in female Sprague-Dawley rats distributed in four experimental groups: ND group (fed a normal diet), HFD group (fed a high-fat diet) and two additional groups fed the same high-fat diet and supplemented by gavage with 40 mg/kg/day or 400 mg/kg/d of ID-alG™, a seaweed extract obtained from Ascophyllum nodosum in which grape extract is used as carrier. The experimental period length was of 8 weeks.…”
Section: Brown Seaweedmentioning
confidence: 99%
“…A novel compound present in LIS is ID-alG, an ingredient obtained from the thallus of the brown alga Ascophyllum nodosum using Vitis vinifera grape extract as a carrier (<5%). 9 According to Terpend et al, ID-alG is rich in polyphenols, capable of inhibiting intestinal a-amylase and lipase enzymes that could lead to a reduction in glucose and fat absorption rate. Meanwhile, to our knowledge, there are no published studies that have evaluated the potential satiating properties of ID-alG in humans, the reported inhibition in a-amylase activity looks promising, considering that a reduction in glucose absorption ratio might prolong glucose delivery from the intestine and, hence, delay glucopaenia-related hunger signals.…”
Section: Appetite Ratingsmentioning
confidence: 99%
“…According to results from a study carried out in high fat fed rats, ID-alG (a seaweed extract rich in polyphenols derived from phloroglucinol) has inhibitory properties of digestive enzymes such as lipase and a-amylase, capable of reducing fat and carbohydrate absorption rates from the diet. 9 Moreover, it has Food & Function PAPER been reported that consuming Ascophyllum nodosum enriched bread reduces energy intake in obese subjects, 10 suggesting that consumption of this seaweed isolate might also lead to a reduction in energy intake by modulating feelings of hunger and satiety, although the effects of its non-ber extracts have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%